Epigenetic Effects Promoted by Neonicotinoid Thiacloprid Exposure - Hartman, Colin; Legoff, Louis; Capriati, Martina; Lecuyer, Gwendoline; Kernanec, Pierre-Yves; Tevosian, Sergei; D’Cruz, Shereen Cynthia; Smagulova, Fatima (Frontiers in Cell and Developmental Biology, 2021)
Background: Neonicotinoids, a widely used class of insecticide, have attracted much attention because of their widespread use that has resulted in the decline of the bee population. Accumulating evidence suggests potential animal and human exposure to neonicotinoids, which is a cause of public concern. Objectives: In this study, we examined the effects of a neonicotinoid, thiacloprid (thia), on the male reproductive system. Methods: The pregnant outbred Swiss female mice were exposed to thia at embryonic days E6.5 to E15.5 using “0”, “0.06”, “0.6”, and “6” mg/kg/day doses. Adult male progeny was analyzed for morphological and cytological defects in the testes using hematoxylin and eosin (H&E) staining. We also used immunofluorescence, Western blotting, RT-qPCR and RNA-seq techniques for the analyses of the effects of thia on testis. Results: We found that exposure to thia causes a decrease in spermatozoa at doses “0.6” and “6” and leads to telomere defects at all tested doses. At doses “0.6” and “6”, thia exposure leads to an increase in meiotic pachytene cells and a decrease in lumen size, these changes were accompanied by increased testis-to-body weight ratios at high dose. By using RNA-seq approach we found that genes encoding translation, ATP production, ATP-dependent proteins and chromatin-modifying enzymes were deregulated in testes. In addition, we found that exposure to thia results in a decrease in H3K9me3 levels in spermatocytes. The changes in H3K9me3 were associated with a dramatic increase in activity of retroelements. Conclusions: Our study suggests that gestational exposure to thia affects epigenetic mechanisms controlling meiosis which could lead to deleterious effects on male spermatogenesis.